The unintended consequence of Financial Fair Play: An examination of competitive balance across five European football leagues - Plumley, D.; Ramchandani, G. M.; Wilson, R. (Sport, Business and Management, 2018)
Purpose: The purpose of this paper is to examine competitive balance in European football leagues before and after the inception of Financial Fair Play (FFP) regulations by Union of European Football Associations in 2011, designed to bring about financial stability and improve competitive balance in the European game. Design/methodology/approach: The research focuses on the top division football leagues in England (English Premier League), Germany (Bundesliga), France (Ligue 1), Italy (Serie A) and Spain (La Liga). The paper is organised into two distinct time periods: pre-FFP, comprising the six seasons between 2005/2006 and 2010/2011; and post-FFP, comprising the six seasons between 2011/2012 and 2016/2017. The paper uses recognised measures of concentration and dominance to measure competitive balance. Findings: The results show a statistically significant decline in competitive balance post-FFP for leagues in Spain, Germany and France but not for England and Italy. Furthermore, the results report significantly higher levels of concentration and dominance by a select number of clubs in Germany. Originality/value: The paper is one of the first to analyse competitive balance in this way both pre- and post-FFP. Whilst the paper cannot demonstrate a causal link between FFP and competitive balance, there are strong indications that competitive balance has been adversely affected (for some leagues) since the regulations have been imposed. To that end, the paper argues that FFP has had "unintended consequences" in respect of competitive balance.